2018
DOI: 10.1016/j.surfcoat.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical properties and microstructural modifications in electrodeposited Fe-W alloys through controlled heat treatments

Abstract: Among W alloys, FeW has seen much attention recently, due to the need of moving toward the design of environmentally friendly materials. Coatings with 4, 16 and 24 at.% of W were electrodeposited from an environmental friendly Fe(III)-based glycolate-citrate bath. The samples were annealed in vacuum at different temperatures up to 800 °C. Different crystalline phases are formed upon annealing: α-Fe, Fe2W, Fe3W3C, Fe6W6C, and FeWO4. Their grain size and distribution within the coating was studied by means of El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…This opens the window for alternative, durable, cost-effective materials that would be suitable for replacement of noble metals. Among various alternatives, W(Mo)-based alloys with iron group metals, namely Ni, Co and Fe, have attracted considerable research attention during the last decades because of their high electrocatalytic activity [9e11], superior mechanical [12,13], tribological [14e16], anti-corrosion properties [15] and thermal resistance [18,19]. W(Mo) alloy electrodes with iron group metals have been prepared by various methods, such as magnetron sputtering [10,20,21], hydrothermal treatment [22], arc melting [23], mechanical alloying [24e27] and electrodeposition [28e30].…”
Section: Introductionmentioning
confidence: 99%
“…This opens the window for alternative, durable, cost-effective materials that would be suitable for replacement of noble metals. Among various alternatives, W(Mo)-based alloys with iron group metals, namely Ni, Co and Fe, have attracted considerable research attention during the last decades because of their high electrocatalytic activity [9e11], superior mechanical [12,13], tribological [14e16], anti-corrosion properties [15] and thermal resistance [18,19]. W(Mo) alloy electrodes with iron group metals have been prepared by various methods, such as magnetron sputtering [10,20,21], hydrothermal treatment [22], arc melting [23], mechanical alloying [24e27] and electrodeposition [28e30].…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that the hardness of Fe-24at.%W coatings was significantly increasing after annealing treatment at 400°C, and it was reaching a maximum of 16.5 GPa upon annealing at 600°C. The maximum in the hardness was related to the partial crystallization of the Fe-24at%W coatings with the formation of a-Fe crystalline phase when annealing at 600°C, as revealed by XRD analysis [10]. However, XRD analyses did not reveal any microstructural transformation in the Fe-W coatings that could explain the substantial increase in the hardness (about 20%) obtained already at 400°C.…”
Section: Introductionmentioning
confidence: 82%
“…Furthermore, the hardness of Fe-W coatings can even be increased by heat treatments. In a previous work, Mulone et al [10] investigated the effect of heat treatments on microstructure and mechanical properties of Fe-W coatings electrodeposited with various W contents. The authors observed that the hardness of Fe-24at.%W coatings was significantly increasing after annealing treatment at 400°C, and it was reaching a maximum of 16.5 GPa upon annealing at 600°C.…”
Section: Introductionmentioning
confidence: 99%
“…For spray‐coating, especially plasma spraying, although researchers have obtained diverse solid surface coatings on metals showing favorable mechanical and thermal shock resistance, the complexity of the monolithic substrate geometry is a major limitation on the application of this technology ,. The performance of the coating prepared by EPD method depends on many factors like the working parameters of the set‐up equipment, the properties of the suspension and the duration of the deposition . CVD method requires harsh environment condition and continuous optimizations to enhance the deposition rate and to obtain a very thin layer evenly and completely to cover the reactor chamber .…”
Section: Introductionmentioning
confidence: 99%